Soil erosion management using The Soil and Water Assessment Tool (SWAT) model in Semantok Watershed - Oktavia Triana Kurniawati; Dian Sisinggih; Very Dermawan (Universitas Wiralodra, 2024)
The land use characteristics in the Semantok watershed have a significant impact on the reservoir's usable age. According to the land use patterns, including teak woods, rice fields, moorlands, dry fields, and residential areas, the Semantok watershed has the capacity to carry sediment when it rains. One of the models to analyze surface runoff and sediment is the Soil and Water Assessment Tool (SWAT). SWAT was developed to predict the impact of land management practices on water, sediment and agricultural chemical yields in large complex watersheds with varying soils, land use and management conditions over long periods of time. The purpose of this research is to quantify the amount of erosion and sedimentation that results from land use changes in the Semantok watershed in 2015 and 2021 and to determine management scenarios that can reduce the value of erosion and sedimentation that can implemented upstream of the Semantok dam using SWAT. The data used for the research are climatology data, DEM map, landuse map, and river data. The amount of erosion at the Semantok watershed outlet increased from 7.00 mm/year in 2015 to 14.18 mm/year in 2021. Based on Forestry Ministerial Regulation No. P.61/Menhut-II/2014, the Semantok watershed's carrying capacity is 3.95 falling into the pretty bad category (3.5 < DDD < 4.3). Three scenarios were compared in order to carry out control efforts: revegetation, check dams, and combining revegetation and check dams. The most efficient way to reduce erosion by up to 30.51% is to combine revegetation and check dam.